What makes the question relevant from the educational point of view? On the subject universe of educational studies in the context of their scientific development - Agata Łopatkiewicz (Jan Dlugosz University, 2022)
Is a question asked by an educational researcher an educational question? What makes the question relevant from the educational point of view? What is the significance of the way of thinking about the development of educational studies as a scientific discipline? The aim of the article is an attempt to formulate answers to these questions. They have been articulated in the context of reflection on the scope and content of the subject universe of educational studies. Distinguishing two basic ways of thinking about the development of this discipline - as an expansion and continuation - allows to bring out and highlight the differences in defining what is educational, and what has a reflection on the scope and content of research questions posed by educational researchers.